The Influence Of Board Characteristics On Company Profit Management With Family Ownership Structure As A Moderation - Octavia Octavia (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
An entity's financial reports play a very important role in decision making for investors. However, many individuals are irresponsible in implementing earnings management, which makes investors have a bad assessment of this practice. The aim of this research is to measure how the characteristics of the board of directors can impact earnings management by using family ownership structure as a moderator. The data sample used in this research is entities operating in the non-financial sector on the IDX from the 2018-2022 period. Of course, this research carried out selection in collecting data using the purposive sampling method. This research uses multiple linear regression which uses Eviews and SPSS as software used in processing research data. The results of the research show that (i) the size of the board of directors has a significant effect on earnings management, (ii) the number of independent boards does not affect management, (iii) the percentage of the board of directors with expertise influences the increase in earnings management, (iv) the lower the female board of directors, the lower the practice of earnings management, (v) using family ownership as a moderation can weaken the relationship between the board of directors and earnings management